Comparison of short course radiotherapy with chemoradiotherapy for locally advanced rectal cancers in the elderly: A multicentre, randomised, non-blinded, phase 3 trial. (February 2023) - François, Eric; De Bari, Berardino; Ronchin, Philippe; Nouhaud, Elodie; Martel-Lafay, Isabelle; Artru, Pascal; Clavere, Pierre; Vendrely, Veronique; Boige, Valerie; Gargot, Deny; Lemanski, Claire; De Sousa Carvalho, Nicolas; et al.
Abstract: Background: There is no specific guideline for the treatment of locally advanced rectal cancers in the elderly. Here we compared R0 resection rate and degradation of autonomy based on the instrumental activities of daily living score between neoadjuvant, short course radiotherapy and chemoradiotherapy in this specific population. Patients and methods: Patients ≥75 years with resectable T3–T4 rectal adenocarcinoma within 12 cm of the anal verge or T2 of the very low rectum were randomised between short course radiotherapy (5 × 5 Gy in one week) and chemoradiotherapy (50 Gy, 2 Gy/f, 5 weeks with capecitabine: 800 mg/m 2 twice daily, 5 days per week), with delayed surgery 7 ± 1 weeks for the two arms. Results: One hundred and three eligible patients were enrolled between January 2016 and December 2019 when the trial was closed due to poor accrual. The R0 resection rate (first co-primary objective) was 84.3%; confidence interval 95% [73.26–94.18] in the short course group and 88%; confidence interval 95% [77.77–96.60] in the chemoradiotherapy group (non-inferiority p = 0.28). The deterioration of the instrumental activities of daily living score was not different during the pre-operative phase, it was significantly more deteriorated in the chemoradiotherapy group at 3 months post-operative (44.8% versus 14.8%; p = 0.032) but was not different at 12 months post-operative (second co-primary objective). During pre-operative phase, 9.8% of patients in short course group and 22% of patients in chemoradiotherapy group presented a serious adverse event, but we observed no difference during the post-operative phase between the two groups. Conclusion: Although the main objectives of the study were not achieved, the short course radiotherapy followed by delayed surgery could represent a preferred treatment option in patients ≥75 years with locally advanced rectal cancer; a new study must be performed to confirm the improvement in overall and specific survival results. Highlights: This is the first randomised study for locally advanced rectal cancers in the elderly. The R0 resection rate and the preservation of autonomy were the two co-primaries. We could not confirm the non-inferiority of 5 × 5 radiotherapy for the co-primary R0. The tolerance was better for short course radiotherapy.